Effect of Methomyl on Growth, Antioxidant System of GIFT (Oreochromis niloticus), and Residue in the Presence of Water Spinach (Ipomoea aquatica Forsk). (12th August 2022) - Jing, Xiaojun; Zheng, Yao; Mulbah, James P.; Chen, Jiazhang; Xu, Gangchun
Abstract : This study was conducted to investigate the effect of methomyl (MET) on the growth and antioxidant system of GIFT (5.28 ± 0.12, n = 180) in the presence of water spinach ( Ipomoea aquatica ) aas a floating bed. Four treatment groups have been established, named control (0), 2, 20, and 200 μ g/L MET. Results showed that at moderate temperatures such as 25°C to 30°C, tilapia's feed consumption increased and body weight improved. SOD, CAT, and GSH in the liver of GIFT indicated the significant increase under MET exposure. MET reduced the growth rate of GIFT, and water spinach reduced part of the water quality indexes in the MET (<200 μ g/L) groups. Water spinach altered GIFT's hepatic oxidation system to some extent and effectively absorbed MET in water and transferred it to itself, and the degradation time was lower than the dietary standard time which termed as 15–20 days. Growing water spinach in farmed waters partially decomposes MET and prevents it from causing damage to GIFT's liver.